[Breeding of Pied flycatcher (Ficedula hypoleuca) in Ossola Valley (Verbano-Cusio-Ossola, Piedimont)] - Radames Bionda (Rivista Italiana di Ornitologia - Research in Ornithology)
We report a nesting case of the Pied flycatcher Ficedula hypoleuca, in Ossola Valley, Verbano Cusio Ossola province, northern Piedmont. Nesting took place in a nest box positioned on an oak tree at the edge of a clearing at 1075 m altitude, occupied by the pair at the end of May. A month later, the nest box collapsed during a heavy thunderstorm, and the 6 chicks present were found dead.